Adverse reaction to metal debris due to fretting corrosion between the acetabular components of modular dual-mobility constructs in total hip replacement: a systematic review and meta-analysis. Issue 5 (4th May 2021) - French, Jonathan M. R.; Bramley, Paul; Scattergood, Sean; Sandiford, Nemandra A.
Abstract : Modular dual-mobility (MDM) constructs can be used to reduce dislocation rates after total hip replacement (THR). However, there are concerns about adverse reaction to metal debris (ARMD) as a result of fretting corrosion between the metal liner and shell. This systematic review reports outcomes following THR using MDM components. It was registered with PROSPERO and conducted in line with Cochrane and PRISMA recommendations. Sixteen articles were included overall, with meta-analysis performed on relevant subsets using a random intercept logistic regression model. Estimated median incidence of ARMD requiring revision surgery within study follow-up period was 0.3% (95% CI 0.1 – 1.8%, from 11 cohort studies containing 1312 cases). Serum metal ion levels were mildly raised in 7.9% of cases, and significantly raised in 1.8%, but there was no correlation with worse clinical hip function scores within studies. Dislocation rate was 0.8%. Revision rate was 3.3%. There are mixed reports of wear on the backside of the metal liner from the acetabular shell and screw heads. Both implant design and component malseating are implicated, but currently it is unclear to what extent each factor is responsible. Studies were poor quality with high risk of confounding, especially from trunnion corrosion. We have made recommendations for further work. In the meantime, surgeons should be aware of the potential risk of ARMD when considering using an MDM prosthesis, and, if selecting one, must ensure proper seating of the liner and screws intraoperatively. Cite this article: EFORT Open Rev 2021;6:343-353. DOI: 10.1302/2058-5241.6.200146